High-ET dijet photoproduction at HERA - Chekanov, S; Derrick, M; Magill, S; Musgrave, B; Nicholass, D; Repond, J; Yoshida, R; Mattingly, M; Jechow, M; Pavel, N; Yagües Molina, A; Antonelli, S; et al. (2007)
The cross section for high-ET dijet production in photoproduction has been measured with the ZEUS detector at HERA using an integrated luminosity of 81.8pb-1. The events were required to have a virtuality of the incoming photon, Q2, of less than 1GeV2 and a photon-proton center-of-mass energy in the range 142<wγp<293gev. at="" etjet1="" events="" if="" jets="" least="" of="" requirements="" satisfied="" selected="" the="" transverse-energy="" two="" were="">20GeV and ETjet2>15GeV and pseudorapidity (with respect to the proton beam direction) requirements of -1<ηjet1,2<3, with at least one of the jets satisfying -1<ηjet<2.5. The measurements show sensitivity to the parton distributions in the photon and proton and to effects beyond next-to-leading order in QCD. Hence these data can be used to constrain further the parton densities in the proton and photon. © 2007 The American Physical Society.</wγp<293gev.>